A Study on Doubao AI-Assisted Chinese Oral Teaching Practice for Indonesian Primary School Students - Yingyan Chen; Shuyan Zhang; Xinqiu Zeng; Ling Qin; Iin Afidha Aulia (Nexus Publishing, 2026)
In Chinese language teaching for Indonesian primary school students, learners have long faced insufficient opportunities for meaningful language input and oral output, limiting the development of communicative competence. This study investigates the use of Doubao AI as an auxiliary tool to support Chinese oral instruction. The participants were 30 students from a cross-grade combined class of Grades 5 and 6 at Dezhi School in Malang, Indonesia. The research employed classroom teaching practice using a pre-post comparative design, supported by classroom observation and systematic data recording. The findings indicate that integrating Doubao AI increased students’ exposure to target language structures, encouraged more active classroom participation, and provided additional opportunities for oral interaction through contextualized learning tasks and immediate feedback. Students also demonstrated greater willingness to communicate in Chinese during classroom activities. However, several limitations were identified, including inaccuracies in speech recognition, translation errors, limited pronunciation correction, and insufficient personalized instructional support. These issues reduced the effectiveness of AI in certain learning situations and required continuous teacher intervention. Therefore, while Doubao AI shows considerable potential as a supplementary tool for enhancing Chinese oral teaching in overseas primary schools, it cannot replace teachers, who remain essential for providing pedagogical guidance, language correction, classroom management, and ensuring safe and effective AI-assisted learning.